Empowering marginalized Filipinos through participatory video production - Tojos, Leticia S. (Plaridel : A Philippine Journal of Communication, Media, and Society, 2007)
This article documents the experiences of the Research and Extension for Development Office, College of Social Work and Community Development (REDO, CSWCD) of the University of the Philippines (UP) in producing videos using participatory approaches. In capturing the events and processes, the construct of participatory video production (PVP) has been enriched and a framework in the context of development work in the Philippine setting has been developed. Moreover, its practicability as an organizing and advocacy tool by low income and marginalized Filipinos has been demonstrated.